Expression and Roles of the Immunoglobulin Superfamily Recognition Molecule Sidekick1 in Mouse Retina - Yamagata, Masahito; Sanes, Joshua R. (Frontiers in Molecular Neuroscience, 2019)
Processes of >100 types of interneurons (bipolar and amacrine cells) and projection neurons (retinal ganglion cells, RGCs) for specific and stereotyped patterns of connections in the inner plexiform layer (IPL) of the mouse retina. Four closely related homophilic immunoglobulin superfamily recognition molecules (Sidekick [Sdk] 1, Sdk 2, Dscam and DscamL1) have been shown to play roles in patterning neuronal arbors and connections in chick retina, and all but Sdk1 have been shown to play related roles in mice. Here, we compare patterns of Sdk1 and Sdk2 expression in mouse retina and use genetic methods to assess roles of Sdk1. In adult retina, 3 neuronal types express sdk1 but not sdk2 at detectable levels, 4 express sdk2 but not sdk1 and 3 express both. Patterns of gene expression and protein localization at or near synapses are established during the first postnatal week. Dendrites of amacrine cells and RGCs that express sdk1 but not sdk2 arborize in the same narrow stratum in the center of the IPL. In the absence of Sdk1, this laminar restriction is disrupted. Overexpression of sdk1 in developing cells that normally express sdk2 reorients their dendrites to resemble those of endogenously Sdk1-positive cells, indicating that Sdk1 plays an instructive role in patterning the IPL. Sdk1 fails to affect arbors when introduced after they are mature, suggesting that it is required to form but not maintain laminar restrictions. The effect of ectopically expressed sdk1 requires the presence of endogenous Sdk1, suggesting that the effect requires homophilic interactions among Sdk1-positive neurites. Together with previous results on Sdk2, Dscam, DscamL1, as well as the related Contactins, our results support the idea than an elaborate immunoglobulin superfamily code plays a prominent role in establishing neural circuits in the retina by means of tightly regulated cell type-specific expression and homophilically restricted intercellular interactions.